Impact of Harness Attachment Point on Kinetics and Kinematics During Sled Towing. Issue 3 (March 2016) - Bentley, Ian; Atkins, Steve J.; Edmundson, Christopher J.; Metcalfe, John; Sinclair, Jonathan K.
Abstract : Abstract: Bentley, I, Atkins, SJ, Edmundson, CJ, Metcalfe, J, and Sinclair, JK. Impact of harness attachment point on kinetics and kinematics during sled towing. J Strength Cond Res 30(3): 768–776, 2016—Resisted sprint training is performed in a horizontal direction and involves similar muscles, velocities, and ranges of motion (ROM) to those of normal sprinting. Generally, sleds are attached to the athletes through a lead (3 m) and harness; the most common attachment points are the shoulder or waist. At present, it is not known how the different harness point's impact on the kinematics and kinetics associated with sled towing (ST). The aim of the current investigation was to examine the kinetics and kinematics of shoulder and waist harness attachment points in relation to the acceleration phase of ST. Fourteen trained men completed normal and ST trials, loaded at 10% reduction of sprint velocity. Sagittal plane kinematics from the trunk, hip, knee, and ankle were measured, together with stance phase kinetics (third footstrike). Kinetic and kinematic parameters were compared between harness attachments using one-way repeated-measures analysis of variance. The results indicated that various kinetic differences were present between the normal and ST conditions. Significantly greater net horizontal mean force, net horizontal impulses, propulsive mean force, and propulsive impulses were measured ( p < 0.05). Interestingly, the waist harness also led to greater net horizontal impulse when compared with the shoulder attachment ( p < 0.001). In kinematic terms, ST conditions significantly increased peak flexion in hip, knee, and ankle joints compared with the normal trials ( p < 0.05). Results highlighted that the shoulder harness had a greater impact on trunk and knee joint kinematics when compared with the waist harness ( p < 0.05). In summary, waist harnesses seem to be the most suitable attachment point for the acceleration phase of sprinting. Sled towing with these attachments resulted in fewer kinematic alterations and greater net horizontal impulse when compared with the shoulder harness. Future research is necessary in order to explore the long-term adaptations of these acute changes.